Visualization of giant Mimivirus in a movie for biology classrooms - Kanako Morioka; Ayumi Fujieda; Masaharu Takemura (Journal of Microbiology & Biology Education, 2024)
ABSTRACT We have developed a new observation chamber for Mimivirus-infected Acanthamoeba to create dynamic visual teaching materials for virus education suitable for high school and university biology courses. We conducted experiments and captured a movie showcasing the infection process of Acanthamoeba cells by mimiviruses. In this educational film, we successfully recorded the active movement of healthy Acanthamoeba cells across the surface of a culture flask under an agarose gel. After Mimivirus infection, the movement of the Acanthamoeba cells gradually slowed and eventually stopped. This cessation coincided with the development of the Mimivirus virion factory, which began producing new virions on the surface of the host cells. Moreover, we captured continuous footage of a single cell throughout the viral proliferation process, thereby illustrating the viral proliferation in real time. This educational movie, which visually demonstrates the proliferation of Mimivirus within host cells, acts as an effective teaching tool. Moreover, it enhances students’ understanding of virus proliferation mechanisms and highlights the biological significance of viruses, their impact on host cell fate, and their role in ecosystems.